Digital Public Relations Strategies to Increase Public Awareness Through Instagram at the Aceh Foundation for Children with Disabilities - Diana Permatasari; Suwandi Sumartias; Iwan Koswara (Asosiasi Dosen Muda Indonesia, 2026)
The low level of public awareness of the role and activities of the Aceh Foundation for the Education of Children with Disabilities (YPAC) in educating children with disabilities requires an effective communication strategy through digital media. This study focuses on YPAC Aceh's digital public relations strategy in increasing public awareness through Instagram social media management, including planning, implementation, and evaluation of digital communication. The research method used is a qualitative approach with a descriptive research type, through data collection techniques in the form of interviews, observation, and documentation. The results of the study indicate that YPAC Aceh has implemented a digital public relations strategy in stages through the delivery of visual content based on school activities, interaction with the audience, and simple evaluation of follower responses. Although Instagram management still faces limitations in human resources and is not yet optimally structured, the use of Instagram is considered effective in disseminating information, building empathy, and increasing public awareness of children's disability issues and the role of YPAC Aceh.